2015
DOI: 10.9745/ghsp-d-15-00051
|View full text |Cite
|
Sign up to set email alerts
|

Care Groups I: An Innovative Community-Based Strategy for Improving Maternal, Neonatal, and Child Health in Resource-Constrained Settings

Abstract: Care Groups use volunteers to motivate mothers to adopt key MCH behaviors. The volunteers meet as a group every 2–4 weeks with a paid facilitator to learn new health promotion messages. Key ingredients of the approach include: peer-to-peer health promotion, selection of volunteers by the mothers, a manageable workload for the volunteers (no more than 15 households per volunteer), frequent (at least monthly) contact between volunteers and mothers, and regular supervision of the volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(123 citation statements)
references
References 17 publications
5
117
1
Order By: Relevance
“…Beyond the inclusion of trusted family and community members in community interventions, another potential platform for integrating maternal nutrition interventions and facilitating behaviour change is through Care Groups, which consist of volunteer community‐based health educators who visit 10–15 neighbours to share information on various health topics. The implementation of the Care Group model has been documented in 28 countries (Perry et al, ) and has demonstrated improved breastfeeding rates and receipt of maternal multiple micronutrient supplementation (George et al, ). This community‐based model may provide an opportunity to discuss information on maternal diet with mothers and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the inclusion of trusted family and community members in community interventions, another potential platform for integrating maternal nutrition interventions and facilitating behaviour change is through Care Groups, which consist of volunteer community‐based health educators who visit 10–15 neighbours to share information on various health topics. The implementation of the Care Group model has been documented in 28 countries (Perry et al, ) and has demonstrated improved breastfeeding rates and receipt of maternal multiple micronutrient supplementation (George et al, ). This community‐based model may provide an opportunity to discuss information on maternal diet with mothers and their families.…”
Section: Discussionmentioning
confidence: 99%
“…According to Perry et al [20], similar care group projects in Cambodia, Mozambique, Malawi, Kenya and Rwanda have resulted in huge decline in mortality for children below 5 years and also improved outcomes for key maternal, infant and young child health indicators. The care group approach showed a ripple effect especially in Chiredzi district where several livelihood projects such as fisheries and piggery where initiated discussed during care groups are being driven by men in full support of the motive for household optimal nutrition status.…”
Section: Discussionmentioning
confidence: 99%
“…A care group is a group of 10-15 volunteers, community-based health educators who regularly meet together with project staff for training and supervision [20]. The care group model is an innovative community-based strategy for improving nutrition, maternal, neonatal, and child health in resource-constrained setting [21,22]. Generally, care groups increase coverage and behaviour change by creating a large network of volunteer women [23].…”
Section: The Care Group Model Being Implemented In Zimbabwementioning
confidence: 99%
“…The project applied an integrated PM2A approach to improve food security and reduce chronic malnutrition of vulnerable women and children under age 5. This entailed providing a comprehensive package of interventions that included supplementary feeding for pregnant or lactating women and children under 2 years (i.e., 6–23 months); increasing availability of and access to food through sustainable livelihoods interventions that included use of farmer groups, which cultivated group block farms using improved technology; strengthening facility and community health and nutrition services, including implementation of the Essential Nutrition Actions framework; and increasing access to primary education 6 8 …”
Section: Launch Projectmentioning
confidence: 99%